Preliminary study on fluid bolus administration for prevention of spinal hypotension in dogs undergoing elective cesarean section - Antończyk, Agnieszka; Kiełbowicz, Zdzisław; Niżański, Wojciech; Ochota, Małgorzata (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effect of fluid bolus administration during epidural anesthesia (coload) in female dogs scheduled for elective cesarean section (CS). Hypotension is one of the most common complications of epidural (EA) and spinal (SA) analgesia, and in the case of cesarean section, it may pose a significant risk for placental perfusion and subsequent fetal vitality and puppy survival. Pregnant bitches scheduled for elective CS underwent EA with (treatment group) or without (control group) intravenous fluid bolus administration. The following parameters were measured and compared between both groups: HR, RR, etCO2, SpO2, systolic, diastolic and mean arterial blood pressure were measured at three time points (T1: before surgery, T2: after the last puppy removal, and T3: end of surgery) in dams; vitality (Apgar score at 0, 5, and 20 min) and umbilical cord blood parameters (pH, pCO2, HCO3, base excess, lactate and glucose) in newborns. The results indicated that crystalloid coloading increased maternal systolic, diastolic, and mean blood pressure (treatment vs. control group, 101.46±9.18, 48.01±13.47, and 67.07±13.15 mmHg vs. 80.68±7.29, 36.52±8.75, and 180 52.30±7.77, p<0.05) with significantly fewer episodes of hypotension. Additionally, puppies in the treatment group received higher scores in the 5-minute (7.91±1.67 vs. 6.74±2.20) and 20-minute (9.38±0.87 vs. 8.39±2.50) assessments without the favorable effect on umbilical blood gas parameters. Based on the obtained results, it can be stated that crystalloid coload offers an effective option in cases of hypotension during cesarean section, with clear benefits for both mothers and newborns.